Ten years on.The Youth Olympic Games (YOG) through the eyes of australian athletes - Grayson, Suzanne Frances (Πανεπιστήμιο Πελοποννήσου, 2020)
The purpose of this thesis is to examine some of the claims of the Olympic Movement through the eyes of Australian athletes at the latest summer Youth Olympic Games (YOG) of 2018. The dissertation takes a different approach from most previous scholarship that has largely concentrated on the peculiarities of the YOG, like the new sport event formats, legacy aspects related to the athletes, and the educational programme. It discusses the role of the athletes themselves, which is rare in the literature and non-existent in terms of Australian participants who have represented their country at all the games. As well as an academic interest in the subject, I also have a personal interest as a former Olympian. I represented Australia in the marathon at the Olympic Games in Atlanta in 1996, some years before the YOG existed.
Keywords: Youth Olympic Games - Sustainability; Youth Olympic Games - Management; Olympic movement; Olympism; Ολυμπιακοί Αγώνες Νέων - Βιωσιμότητα; Ολυμπιακοί Αγώνες Νέων - Διοίκηση και Οργάνωση; Ολυμπιακό κίνημα; Ολυμπισμός